KOMPETENSI DI DUNIA REALITAS SETELAH LULUS SMA - Putlia, Grace; Sundoro, Hary S; Alvita, Meilisa; Wijaya, Brendi; Wardhana, Ali; Rowena, Janny; Wilson, Nicholas; Budi, Budi; Samuel, Samuel (Universitas Bunda Mulia, 2020)
Considering that teenagers in the future will be the next generation, the future must be approved. Tri Dharma of higher education related to Pengabdian Kepada Masyarakat (PKM), which refers to the responsibilities of teachers including transferring, transforming, and using knowledge from within the campus for the community. Based on this, Bunda Mulia University conducted PKM activities by raising the topic